Fractional integration and the dynamics of UK unemployment - Luis A. Gil-Ala\~na; Brian Henry (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
This article is concerned with the dynamic behaviour of UK unemployment. However, instead of using traditional approaches based on I(0) stationary or I(1) (integrated and/or cointegrated) models, we use the fractional integration framework. In doing so, we allow for a more careful study of the low frequency dynamics underlying the series. The conclusions suggest that the UK unemployment may be explained in terms of lagged values of the real oil prices and the real interest rate, with the order of integration of unemployment ranging between 0.50 and 1. Thus, unemployment shows the characteristics of long memory but is mean reverting.
urn:nbn:de:kobv:11-10047180
Keywords: C22; C32; C52; E24; 330; long memory; unemployment; fractional integration